MODELLING OF BUSINESS PROCESSES TO CREATE AN INFORMATION SYSTEM FOR MANAGING THE QUALITY OF A BIOECONOMY ENTERPRISE - VIENAŽINDIENĖ, Milita; СHORNA, Ludmila; KOVALENKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article contains the results of research on modeling business processes for a bioeconomy enterprise. Modeling procedures are related to the distribution of management processes by scale and taking into account the peculiarities of production and management of the enterprise. The modeling procedure itself is necessary to determine each business process, its owners, results, the need to control and save information about its execution. Business processes of the bioeconomy can be divided into mandatory in accordance with the legal framework and reporting of all enterprises, production and management, taking into account the profile of the development of the enterprise. Modeling allows you to determine all production and information flows, control indicators. The results of modeling are a clear visualization, a description of the process. The documentation contains the sequence of all procedures, their provision and control. The proposed concept combines mandatory procedures for accounting for emissions, the implementation of environmental legislation and the introduction of a full production cycle at a bioeconomy enterprise. The adapted concept of mirrors for modeling the actual business processes of creating a balanced system of indicators for the enterprise involves the introduction of new sections, in the general projection Production. When introducing new management technologies, in particular, lean production, it is envisaged to make changes to the company's development strategy, implement procedures for restructuring production processes and retrain staff. An analysis of the life cycle of a bioeconomy enterprise shows that each of its phases requires a reassessment of strategic indicators and business processes. This approach allows you to combine the development strategy of the bioeconomy enterprise and its business processes into one whole. Known modeling techniques and tools based on information technologies can be used for modeling, analysis and optimization, provided that adapted model templates are formed for each specific enterprise. Among the known concepts of the use of business processes, the most relevant are the use of a quality management system and the formation of three mirror models of production and management processes, taking into account the features of environmental legislation and bioeconomy production processes.The proposed concept of modeling business processes can be the basis for making changes to the quality system and management of a bioeconomy enterprise.
Keywords: bioeconomy; information system; modeling; enterprise management; management; business process; business process management